2008
DOI: 10.1534/genetics.107.085977
|View full text |Cite
|
Sign up to set email alerts
|

A Suppressor Screen in Chlamydomonas Identifies Novel Components of the Retinoblastoma Tumor Suppressor Pathway

Abstract: The retinoblastoma (RB) protein is a eukaryotic tumor suppressor and negative cell-cycle regulator. Chlamydomonas reinhardtii cells that lack the RB homolog MAT3 show loss of size checkpoint control and deregulated cell-cycle progression leading to the production of tiny cells. We carried out an insertional mutagenesis screen to isolate bypass suppressors of mat3 (smt mutants) that reverted the mat3 cell-size defect. Previously we reported that the loci encoding Chlamydomonas homologs of E2F and DP were freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…8). As shown in green algae 4,[13][14][15] , the DRBR C. merolae cell enters into the S phase even before growing to a certain threshold size (Fig. 6).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…8). As shown in green algae 4,[13][14][15] , the DRBR C. merolae cell enters into the S phase even before growing to a certain threshold size (Fig. 6).…”
Section: Discussionmentioning
confidence: 66%
“…This observation led us to investigate two types of cell cycle regulators, one that accumulates in association with the cell growth and another that is regulated by circadian rhythms. A key regulator of the G1/S transition in eukaryotic cells, including eukaryotic algae 4,[13][14][15] , is the retinoblastoma (RB) tumour suppressor pathway 16 . RB represses the G1/S transition by binding to the E2F-DP heterodimer, which in turn binds certain specific cis elements of S-phase genes.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that the RB pathway in C. reinhardtii is important for size checkpoint control and size-mediated cell division (Umen and Goodenough, 2001;Fang et al, 2006). The C. reinhardtii RBR homolog is encoded by a single gene, MAT3.…”
mentioning
confidence: 99%
“…mat3 mutants pass commitment at a smaller size than normal but remain in G1 for a normal period of time before entering S/M, where they undergo supernumerary cell divisions to produce tiny daughter cells. Mutations in the C. reinhardtii E2F1 and DP1 genes could suppress the mat3 size defect, indicating that the overall architecture of the RBR pathway is conserved in C. reinhardtii, with MAT3/RBR serving as a negative regulator of E2F-and DP-related proteins (Fang et al, 2006;Olson et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation